2017
DOI: 10.1080/00222895.2017.1341378
|View full text |Cite
|
Sign up to set email alerts
|

Lassoing Skill Through Learner Choice

Abstract: The authors examined several issues related to the motor learning benefits resulting from giving learners choices. In 2 experiments, participants practiced a novel task, throwing a lasso. In Experiment 1, giving learners a choice ostensibly irrelevant to performance (color of mat under target) resulted in enhanced learning relative to a control group. The choice group also reported more positive affect. Experiment 2 compared the effectiveness of task-irrelevant (mat color) versus task-relevant (video demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…There is also increasing evidence that providing even small or incidental choices that do not have direct task relevance can be sufficient to enhance motor performance or learning. Examples include choosing the golf ball color for a golf putting task (Lewthwaite, Chiviacowsky, Drews, & Wulf, 2015), selecting the particular order of different types of punches in kickboxing (Halperin, Williams, Martin, & Chapman, 2016), and picking the color of a mat to be placed under a target (Wulf, Iwatsuki, Machin, Kellogg, Copeland, & Lewthwaite, 2017). A meta-analysis of research studies on choice effects found that incidental choices can be particularly motivating (Patall, Cooper, & Robinson, 2008).…”
mentioning
confidence: 99%
“…There is also increasing evidence that providing even small or incidental choices that do not have direct task relevance can be sufficient to enhance motor performance or learning. Examples include choosing the golf ball color for a golf putting task (Lewthwaite, Chiviacowsky, Drews, & Wulf, 2015), selecting the particular order of different types of punches in kickboxing (Halperin, Williams, Martin, & Chapman, 2016), and picking the color of a mat to be placed under a target (Wulf, Iwatsuki, Machin, Kellogg, Copeland, & Lewthwaite, 2017). A meta-analysis of research studies on choice effects found that incidental choices can be particularly motivating (Patall, Cooper, & Robinson, 2008).…”
mentioning
confidence: 99%
“…The dates of publication ranged from 1995 to 2018, with a clear focus on the last four years. Seventeen studies were conducted in the USA, 42,45,46,50,5465 six in Brazil, 41,47,6669 four in Germany, 51,7072 two in Canada, 52,53 and one each in Spain 40 and Korea. 48 In total, 1273 participants were included in the 31 trials, at least 644 were females (about 51%; two studies made no specification regarding gender).…”
Section: Resultsmentioning
confidence: 99%
“…Three trials reported category-covering age spans. 65,70,71 Four studies targeted only female participants. 46,50,67,68 Most of the studies were randomised or quasi-randomised controlled trials, usually comparing the learning advantages of self-controlled practice conditions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Normality was assessed using the Shapiro–Wilk test, and if violation of normality was noted, a non-parametric test was considered. Scores were analyzed in a univariate analysis of variance (ANOVA) ( 47 ). For the day 1 training session, scores were analyzed in 2 groups × 15-trial ANOVA with repeated measures on the last factor ( 47 ).…”
Section: Methodsmentioning
confidence: 99%
“…Scores were analyzed in a univariate analysis of variance (ANOVA) ( 47 ). For the day 1 training session, scores were analyzed in 2 groups × 15-trial ANOVA with repeated measures on the last factor ( 47 ). The retention of improvement was assessed by comparing the results of trials 1–5 on day 1 and the results of the same trials on day 2, using a paired samples t -test or the Wilcoxon signed-rank test ( 48 , 49 ).…”
Section: Methodsmentioning
confidence: 99%